Imigração italiana na colônia de Silveira Martins: cotidiano, deslocamento, cultura e sociabilidade (Rio Grande do Sul, 1877-1920) - Pazuch, Giovane (2020)
The research is guided by the perspective of cultural and social history, having as reference the everyday issues, the power of relations, the discussions of memory and the representations. The methodology for the research was instrumentalized by the daily analytical categories, displacement, network, memory, tradition, education and religion, however without neglecting the political, social and economic aspects of Italian immigration. Initially, Silveira Martins arrival and landscapes, the objectives of the colony’s foundation, the occupation of the spaces, the constructions, the facilities, the plantations and the animal breeding to civilize nature are presented. Italian immigrants came to Brazil in search of riches and progress. However, in order for these riches to be extracted from the land and transformed into social, economic and political progress, it was still necessary to overcome the obstacles of the terrain formed by forests, mountains, rivers and wild animals. In Silveira Martins, immigrants undertook a family immigration to occupy the inhospitable spaces of the colony and transform them into habitable places. Following is the daily routine of families at home and work, the absence of women in the historiography on Italian immigration and their contribution to the success of immigration and the colony, agriculture and trade. In rural lots immigrants have worked in joint efforts between relatives and neighbors to overcome the most difficult jobs, which has also strengthened the identity and unity of communities. The immigrants devoted all their efforts to building the colony, developing agriculture and making it possible to sell their agricultural produce. They also fought for the tax collection to be reversed to maintain the roads and bridges within the colony. Another aspect incorporated in the analysis is sociability and religiosity in the Chapel Societies expressed in prayers, devotion to the saints and in social festivals. Religion was essential for the social organization of the immigrants around the chapels, in which they chose the patron saints, the lay priests and the manufacturers. While immigrants on the one hand recognized the power of civil and religious authorities, on the hand, they also knew how to use their power to favor them. The immigrants negotiated with the civil authorities the construction of roads, bridges, commerce, schools and taxation, and with the religious authorities negotiated the coming of the priests and the erection of the parishes. Finally, the questions of culture and education constituted by the memories and traditions expressed in schools, mutual aid societies and monuments, the formation of the Talian as a dialect of integration between the settlers and the influence of culture on education are observed. Children and young people received from their parents the moral education that was reinforced by the Catholic Church and the religious schools. In the family, children learned to work in agriculture, watching the family work and doing manual work, and in school, they learned to read, write, and calculate to sell their products in commerce. The work contributes to the historiography of Italian immigration by studying family sources to deepen knowledge about the history of Italian immigrant families in Rio Grande do Sul. Family documents composed of memories, photographs and genealogies make it possible to reconstruct trajectories individual, family and community groups of people considered common, but which were essential for the success of immigration and colonization in Rio Grande do Sul